The diversity of agromorphological characters of Portulaca grandiflora in the MV8 population deriving from recurrent irradiation - SYARIFAH IIS AISYAH; REGINA AGRITENIA MAYRISCHA SARASWATI; YOSHUA SHANDY YUDHA; WARAS NURCHOLIS (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Aisyah SI, Saraswati RAM, Yudha YS, Nurcholis W. 2022. The diversity of agromorphological characters of Portulaca grandiflorain the MV8 population deriving from recurrent irradiation. Biodiversitas 23: 4432-4439. A multipurpose ornamental plant, Portulaca grandiflora has the value of attractiveness and uniqueness, which lies in various agromorphological characters, primarily in flowers. The potential of P. grandiflora in qualitative characters such as new and unique shapes and colors of the morphology must be enhanced further to increase its economic and aesthetic significance as a floriculture commodity. The induced mutation technique has been proven to improve plants' morphological diversity, and even numerous novel cultivars are produced from artificial mutations. The recurrent irradiation technique was applied in the P. grandiflora mutation breeding program and produced new morphological variations of P. grandiflora until the MV7 generation (seventh generation of the mutation breeding program). The current study aimed to evaluate the diversity of morphological characters of P. grandiflora mutants in the MV8 population resulted from reccurent irradiation technique. Fifty-three selected mutants of P. grandiflora generation MV7 were multiplied by stem cuttings to create an MV8 population. The total MV8 population of P. grandiflora, the result of vegetative propagation, was 1104 plants. The diversity of morphological characters of P. grandiflora in the MV8 population was identified quantitatively (measurement) and qualitatively (visual observation). The results of this study reveal that several P. grandiflora mutants in the MV8 population have a new phenotypic appearance, chiefly in the qualitative characters of flowers. Besides, most of the P. grandiflora MV8 mutant population has inherited identical morphological characters from the previous generation (MV7 population). Further morphological analysis in the next generation needs to be conducted to evaluate the morphological stability of P. grandiflora mutants to develop new cultivars and to investigate the possibility of new phenotypic variations caused by recurrent irradiation treatments.